2000
DOI: 10.1080/14660820052415817
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial magnetic stimulation (TMS): compared sensitivity of different motor response parameters in ALS

Abstract: Owing to the low sensitivity of clinical signs in assessing upper motor neuron (UMN) involvement in ALS, there is a need for investigative tools capable of detecting abnormal function of the pyramidal tract. Transcranial magnetic stimulation (TMS) may contribute to the diagnosis by reflecting a UMN dysfunction that is not clinically detectable. Several parameters for the motor responses to TMS can be evaluated with different levels of significance in healthy subjects compared with ALS patients. The central mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
26
0
1

Year Published

2001
2001
2010
2010

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 0 publications
3
26
0
1
Order By: Relevance
“…One of our most striking findings is that TMS was more sensitive than clinical examination in patients with suspected or possible ALS, revealing UMN dysfunction in 75% (9 of 12) of the upper limbs. The sensitivity of CMCT in supporting the diagnosis reportedly increases with the number of muscles studied, 10,12,14,35,38,40,47 and this may apply to the parameters studied herein. We believe that, as for electromyography, several regions of the body, including muscles innervated by bulbar nerves, should be tested to increase the sensitivity of TMS in supporting a diagnosis of ALS.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…One of our most striking findings is that TMS was more sensitive than clinical examination in patients with suspected or possible ALS, revealing UMN dysfunction in 75% (9 of 12) of the upper limbs. The sensitivity of CMCT in supporting the diagnosis reportedly increases with the number of muscles studied, 10,12,14,35,38,40,47 and this may apply to the parameters studied herein. We believe that, as for electromyography, several regions of the body, including muscles innervated by bulbar nerves, should be tested to increase the sensitivity of TMS in supporting a diagnosis of ALS.…”
Section: Discussionmentioning
confidence: 75%
“…CMCT is reportedly not a sensitive variable for the diagnosis of ALS. 9,14,15,34,40,46,47 A decrease in SP duration 1,11,40,43,45 or an increase in RMT 47 seem to be sensitive variables for diagnosing ALS. By contrast, the amplitude of the MEP is not a reliable marker of UMN dysfunction; even in healthy subjects, MEPs are much smaller than the compound muscle action potentials (CMAPs) evoked by peripheral stimulation.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Several studies showed that the silent period duration, which is a measure of the inhibitory response to TMS from many MUs, is shortened in ALS compared with normal control. 1,12,31,40 However, the silent period, which reflects both spinal and cortical inhibitory processes, is correlated with the size of the excitatory response. 2 The silent period decreases over time in relation to the loss of excitatory responses.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the atrophy of the motor cortex, with severe loss of grey substance (cell body) and its brain connections are highlighted by recent advances in radiology and proton emission through tomography (PET), which quantifies the metabolism of regional areas of motor cortex, associated with quantifying the volume by voxel, making early diagnoses possible 27 . Transcranial magnetic stimulation has become an auxiliary method for early diagnosis through the quantification of the decrease in speed within the motor central nervous system in patients with MND / ALS 28 . Pyramidal signs and muscle atrophy -Characteristically in ALS, the signals of pyramidal release must be present at sites above the sites where the muscular atrophy is evident.…”
Section: Clinical Forms Of Presentationmentioning
confidence: 99%